Oral Microbiota: an Innovative Approach to Colorectal Cancer Diagnosis - Didrikaitė, Gabrielė; Dulskas, Audrius (Lietuvos chirurgija, 2025)
Background. Colorectal cancer is one of the most common and deadly oncological diseases worldwide. Current early diagnostic methods, such as the fecal occult blood test, often lack sufficient sensitivity and specificity, making them potentially unreliable for detecting the disease at an early stage. Recently, an increasing number of studies have highlighted the influence of the microbiota, particularly oral bacteria, on colorectal oncogenesis and their potential use in early diagnostics. The aim of this review is to discuss alterations in the oral microbiota as potential diagnostic biomarkers for colorectal cancer and to assess their reliability and clinical applicability. Methods. This is a literature review analyzing the latest scientific studies selected from the Web of Science, PubMed, Scopus, and ScienceDirect databases. The review examines the translocation of oral microbiota to the gut, their association with intestinal dysbiosis, chronic inflammation, changes in immune response, and the development of colorectal cancer. Results. It was found that certain oral bacterial species, such as Fusobacterium, Porphyromonas, Parvimonas, Faecalibacterium, Rothia, and Tannerella, are frequently detected in colorectal tumor tissues compared to healthy intestinal mucosa. Studies show that these bacteria can migrate from the oral cavity to the gut, colonize the intestinal mucosa, trigger chronic inflammation, and disrupt immune responses and oncogenic regulatory pathways through various mechanisms. Diagnostic models based on oral microbiota taxonomy demonstrated high accuracy (AUC 0.83–0.94) in detecting colorectal cancer, especially when combining saliva and stool samples. Furthermore, some studies suggest that identifying specific oral bacteria may also aid in detecting early precancerous lesions, such as colorectal adenomas, emphasizing their value in early-stage diagnosis. Conclusions. Oral microbiota bacteria hold significant potential as non-invasive and sensitive biomarkers for the early detection of colorectal cancer. In the future, integrating these findings into clinical practice may considerably enhance early diagnostic capabilities for this disease.
Keywords: oral microbiota; colorectal cancer; oncology; biomarker